PENYELESAIAN KASUS TINDAK PIDANA PENGANIAYAAN SEBAGAIMANA DIMAKSUD PASAL 351 AYAT (1) DAN AYAT (2) KUHP JO PASAL 352 MELALUI RESTORATIVE JUSTICE DI WILAYAH POLRESTA PONTIANAK - PUJI PRAYITNO, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2012)
AbstractApplying of Restorative Justice to solving of maltreatment crime case as referred to Section 351 Sentences (1) and (2) Jo Section 352 Criminal Law in Pontianak District Police, assessed enough effective and efficient in : a. builds participation with between perpetrators, victim, and group of public finalizes an event or light crime; b. Places perpetrator, victim, and public as